Ideas behind the new or updated Mediterranean legal instruments - Tullio Scovazzi (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper is mainly concerned with the legal instruments regulating the Mediterranean environment. Co-operation in this field is based on a regional treaty, the Convention on the Protection of the Mediterranean Sea against Pollution, and its relevant protocols. All these instruments constitute the so-called "Barcelona system". The new legal picture of the Mediterranean, however, is not limited to the Barcelona system. There are agreements on marine mammals, fisheries, and another field of future co-operation could be the preservation of a common underwater archaeological and cultural heritage. Many of the new or updated instruments mentioned above have not entered into force yet, more for time-consuming domestic procedures than for lack of political will. The Mediterranean could be considered a primary heritage and concern for the bordering States (and for the EU as well). The regime governing this kind of seas could be oriented towards the protection of the marine environment, the sound management of living resources, the preservation of the common cultural heritage. It would be interesting to evaluate whether the idea of "prime responsibility" (applied in the case of Antarctica) may present some purpose also in the Mediterranean.
Keywords: 330; Umweltabkommen; Umweltrecht; Gewässerschutz; Mittelmeerraum